(untitled) (The Research of Medical Science Review, 2025)
Objectives: The main objective of this study was to establish and compare the diagnostic performance of ZN microscopy and GeneXpert PCR. Study Design: The current study was comparative cross-sectional study. Place and Duration of Study Duration: The current study was conducted at Provincial Reference Laboratory Hayatabad Medical Complex with in the duration of six months from November 2024 to May 2025. Material and Methods: 80 Sputum samples were collected from though patients by using non probability consecutive sampling technique who present clinical sign and symptoms of Tuberculosis including both gender male and females who’s aged were 1 to 80 years while those patients who have other lungs infection or lung diseases were excluded from the current study. Each patient gave two sputum specimens for examination. One sample was tested for acid-fast bacilli using the ZN staining method, while the second was subjected to the GeneXpert MTB/RIF assay. Comparing ZN microscopy’s results with GeneXpert, the reference standard, underpinned evaluation of the performance of ZN microscopy’s prediction. Results: Of this sample of 80 patients, 43 (53.75%) were given the diagnosis of TB. GeneXpert detected each and every single case of TB hence 100% sensitivity and specificity. By contrast, 15 cases were found by ZN microscopy with a sensitivity of 45.45%, specificity 100%. The number for the positive predictive value was 100%, and the negative predictive value was 72% for ZN microscopy. The McNemar test indicated that the two diagnostic methods were significantly different (p = 0.000). Conclusion: GeneXpert PCR demonstrates increased diagnostic potential over ZN microscopy in pulmonary TB, notably increased sensitivity and NPV. Although with limitations, ZN microscopy is still useful in resource-limited domains but the introduction of GeneXpert into TB diagnostics could result into early diagnosis, faster response and better control of TB transmission.